Dzieciobójstwo w dawnych dramatach szkolnych - Mieszek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article is analysing dramas from school theatres written between the 16th and the 18th century, containing the infanticide motive. It is seen that infanticide varies in different plays. In no case was it a main theme of dramas. Infanticide was an important component of the plot in martyrological plays. These dramas showed the heroism of martyrs and concentrated on the details of the felony. At the same time, in other plays, manslaughter of the child constitutes a subplot. Very often, the motive for killing children was the anxiety about loss of power. In many dramas, justification for committing such a crime was more important than the crime itself. Manslaughter of children probably was not portrayed directly on stage, according to the rules included in Ratio Studiorum. It is possible that it was portrayed with the help of allegorical images or with the magic lantern.